Paleochannels of Zerafshan Delta (Boukhara oasis, Uzbekistan): First Luminescence datings - Fouache, Eric (2017)
An ongoing study on the Zerafshan delta, which now forms the double oasis of Bukhara and Qaraqöl, provides an understanding of urban evolution in a semi-arid environment linked to water resources management. In order to determine the chronology of the paleo-channels, a first series of OSL datings was undertaken. With the exception of one branch dating from the last glacial maximum, the others were active from the Neolithic to the early Bronze Age, with a general movement from north-east to south-west. © 2017 Elsevier Masson SAS